Nodal radiotherapy for prostate adenocarcinoma recurrence: predictive factors for efficacy - Gueiderikh, Anna; Baude, Jérémy; Baron, David; Schiappa, Renaud; Katsahian, Sandrine; Moreau, Damien; Laurans, Marc; Bibault, Jean-Emmanuel; Kreps, Sarah; Bondiau, Pierre-Yves; Quivrin, Magali; Lépinoy, Alexis; et al. (Frontiers in Oncology, 2024)
BackgroundNodes are the second site for prostate cancer recurrence. Whole-pelvic radiotherapy (WPRT) has shown superiority over nodal stereotactic body radiotherapy (SBRT) in two retrospective cohorts. We aimed to compare both modalities and assess factors associated with treatment outcomes.Materials and methodsThis retrospective multicentric cohort study included patients from five institutions spanning from 2010 to 2022. Patients had a history of prostatic adenocarcinoma classified as N0 M0 at diagnosis with a first nodal-only pelvic castration-sensitive recurrence. Failure-free survival (FFS) was defined as the time from the end of RT to the first failure event–biochemical or imaging recurrence, or death.ResultsA total of 147 patients (pts) were analyzed, mainly treated for a recurrence after initial prostatectomy (87%), with 64 (43.5%) undergoing SBRT and 83 (56.5%) undergoing WPRT. SBRT was chosen mainly for dosimetric constraints (67%) and was associated with a lower rate of concomitant androgen deprivation therapy (ADT) prescription. With a median follow-up of 68 months [inter-quartile range (IQR) = 51], FFS was significantly lower in the SBRT group (p < 0.0001). In multivariable analysis, WPRT and ADT were associated with a longer FFS. Factors associated with a longer FFS after SBRT included associated ADT, lower prostate-specific antigen (PSA) levels, a PSA doubling time >6 months, and a Gleason score <8. SBRT was associated with a lower rate of genitourinary and gastrointestinal grade ≥2 complications.DiscussionFor an isolated pelvic nodal prostate cancer recurrence, SBRT is associated with a shorter FFS compared to WPRT. SBRT is often more convenient for patients and leaves further pelvic salvage options available, so it can be explored as an option for well-informed patients.